Electrical Design and Drafting Skills Needed by Polytechnic Graduates for Employment in the Oil and Gas Industry in Niger-Delta, Nigeria - Paulinus Chijioke Okwelle; Offia Tugwell Owo; Chima Christain Ibekwe (INVOTEC, 2022)
The study was carried out to assess the skills required by polytechnic graduates for employment in the oil and gas industry in Nigeria's Niger-Delta region. A  descriptive survey was used for the study, whose population comprised 1404 oil and gas industry workers in the Niger-Delta, Nigeria. Purposive sampling technique was used to select from the population, 27 electrical supervisors and 62 electrical graduates as the study sample. One research question and one hypothesis guided the study. A 35-item structured questionnaire designed by the researchers and titled “Electrical Design and Drafting Skills needed by Polytechnic Graduates Questionnaire (EDDSPGQ)” was used to collect information from the respondents. The EDDSPGQ was designed based on the  5-Likert Scale. The instrument was face and content-validated by two industry-based electrical supervisors and another expert in measurement and evaluation. The instrument’s reliability was established via the  Cronbach alpha method, having yielded a coefficient of 0.83.A  mean was used to answer the research question; standard deviation was used to ascertain homogeneity in the responses of the respondents; and a t-test was used to test the hypothesis at a 0.05 level of significance. The study reveals that electrical and electronic graduates need to develop skills in drafting point-point diagrams, control circuits of an automatic re-closure scheme, star-delta starters and three-phase line-in diagrams. Consequently, it was recommended, among others, that the Government should provide modern training facilities in polytechnics as well as make SIWES more effective for the quality skills development of engineering students in preparation for employment in the oil and gas industry in Nigeria upon graduation.